2023
DOI: 10.7759/cureus.49734
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Cardiovascular Diseases: An Update

Farrookh Haider,
Hashsaam Ghafoor,
Omar F Hassan
et al.

Abstract: Vitamin D is a vital nutrient that plays a significant part in several physiological processes within the human body, including calcium metabolism, bone health, immune function, and cell growth and differentiation. It is obtained mainly through exposure to sunlight but can be acquired from certain foods and supplements as well. Vitamin D deficiency (VDD) could be the risk factor for cardiovascular diseases (CVDs), such as heart disease and stroke. In blood vitamin D low levels have been linked with an enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 200 publications
0
1
0
Order By: Relevance
“…It is unclear, nonetheless, if low vitamin D levels are the primary cause or an effect of these disorders. Although some studies suggest that taking supplements of vitamin D may lower the risk of cardiovascular disease (CVD), further study is needed to fully understand the relationship between vitamin D and cardiovascular health (Haider et al, 2023). Numerous observational studies have revealed that VD may shield individuals from stroke (Manson et al, 2019).…”
Section: Determination Of Viscositymentioning
confidence: 99%
“…It is unclear, nonetheless, if low vitamin D levels are the primary cause or an effect of these disorders. Although some studies suggest that taking supplements of vitamin D may lower the risk of cardiovascular disease (CVD), further study is needed to fully understand the relationship between vitamin D and cardiovascular health (Haider et al, 2023). Numerous observational studies have revealed that VD may shield individuals from stroke (Manson et al, 2019).…”
Section: Determination Of Viscositymentioning
confidence: 99%